The Quality of Services Provied by BPJS is A Critical Determinant of Member Satisfaction - Tamimi, Risqia; Anggraeni, Kayla Putri; Khurulaini, Esti; Purnama, Lutfianti Noor Safi’ah; Prasetia, Andika; Mauludi, Uli Rahmatul; Munjiah, Siti (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2025)
The quality of BPJS Health Facilities services has a positive and significant effect on patient satisfaction. Improving the quality of BPJS Health Facilities services is very necessary to increase patient satisfaction and improve the image of the clinic. Health facilities must first improve the quality of service effectively and efficiently, and have high service quality to increase patient satisfaction. The quality of health facility services (Faskes) of the Social Security Administering Agency (BPJS) plays an important role in increasing patient satisfaction. In recent years, BPJS has become one of the largest health insurance providers in Indonesia, with a wide and diverse network of health facilities. However, the service quality of BPJS Health Facilities is still a major concern in increasing patient satisfaction. In this article, the service quality of BPJS Health Facilities is analyzed through several indicators, including waiting time, drug quality, and quality of care. The results show that the high quality of BPJS Health Facilities services has a positive effect on patient satisfaction. Patients who receive services with short waiting times, good quality medicines, and satisfactory quality of care tend to be more satisfied with the services provided. Fee collection by the first health facility also plays an important role in increasing patient satisfaction. The first health facility that is able to cover service costs effectively and efficiently tends to increase patient satisfaction. Thus, improving the quality of primary health care services is very necessary to increase patient satisfaction and improve the image of the clinic.